Implementasi Kebijakan pemberian Beasiswa Dana Otonomi Khusus bagi Mahasiswa Port Numbay Kota Jayapura - Kumbubui , Rudolf Heli; Fatem, Agustinus; Tebay, Vince; Ohoiwutun, Yosephina (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2024)
As an effort to advance Papuan human resources, the Special Autonomy Law regulates education and culture. One form of concern for the future of Papuan human resources, especially attention in the education sector, was also shown by the Jayapura City Government through the Port Numbay Men's Special Education Program (PKP3N) in collaboration with the Universitas Kristen Satya Wacana (UKSW) Salatiga. The provision of scholarships through PKP3N since 2013 until now has shown a fairly good performance despite the challenges and obstacles faced. This sociological condition in the field of Higher Education does not have to be a prolonged problem, but a solution must be sought. Therefore, it is necessary to create a model that is considered appropriate in answering various problems of higher education within the Jayapura City Government. Specifically, the purpose of this research is to explain the implementation of the policy of the scholarship award in the Higher Education Sector implemented by the Jayapura City Government, identify the factors that support and hinder the process of implementing the policy of the scholarship award in the Higher Education Sector for Port Numbay students. at UKSW Salatiga, and strategically evaluating the success of implementing the Special Autonomy Fund scholarship award for the Higher Education Sector within the Jayapura City Government. This study was designed with a qualitative method. Data was collected through structured interviews with policy makers (Jayapura City Government and Jayapura City Regional Secretary) and policy recipients (19 students of UKSW Salatiga). Unstructured interviews were also addressed to policy implementers and several community members. The findings of this study mainly focus on the need for socialization to executive officials, Technical OPD and Community Leaders as well as a form of attention and motivation to policy recipients as a form of follow-up for the success of policy implementation.